Why Females Do Better: The X Chromosomal TLR7 Gene-Dose Effect in COVID-19 - Spiering, Anna E.; de Vries, Teun J. (Frontiers in Immunology, 2021)
A male sex bias has emerged in the COVID-19 pandemic, fitting to the sex-biased pattern in other viral infections. Males are 2.84 times more often admitted to the ICU and mortality is 1.39 times higher as a result of COVID-19. Various factors play a role in this, and novel studies suggest that the gene-dose of Toll-Like Receptor (TLR) 7 could contribute to the sex-skewed severity. TLR7 is one of the crucial pattern recognition receptors for SARS-CoV-2 ssRNA and the gene-dose effect is caused by X chromosome inactivation (XCI) escape. Female immune cells with TLR7 XCI escape have biallelic TLR7 expression and produce more type 1 interferon (IFN) upon TLR7 stimulation. In COVID-19, TLR7 in plasmacytoid dendritic cells is one of the pattern recognition receptors responsible for IFN production and a delayed IFN response has been associated with immunopathogenesis and mortality. Here, we provide a hypothesis that females may be protected to some extend against severe COVID-19, due to the biallelic TLR7 expression, allowing them to mount a stronger and more protective IFN response early after infection. Studies exploring COVID-19 treatment via the TLR7-mediated IFN pathway should consider this sex difference. Various factors such as age, sex hormones and escape modulation remain to be investigated concerning the TLR7 gene-dose effect.